42 Are GP trainees ready to manage palliative care patients independently by completion of training?. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Rowley, Grace; Bell, Jane
Abstract : Background: Palliative care in the community is predominantly carried out by General Practitioners (GPs). As palliative care is part of most GPs workloads then trainees need to be prepared to manage this group of patients by completion of training (CCT). The aim of the study was to find out about GP trainees' exposure to palliative care during training and to explore whether GP trainees felt that they were ready to manage palliative care patients independently by CCT. Methods: Semi-structured interviews were carried out by telephone with ten final year GP trainees. The trainees were voluntarily recruited through the North East GP Vocational Training Scheme. The data was analysed using thematic analysis. Results: The findings emphasise the importance of palliative care experience during training and the value of hospice placements. The findings demonstrated that many of the skills attained through working with palliative patients were transferrable and enhanced the overall practice of the trainees. Opportunities to develop complex communication skills were particularly valued by the trainees. The interviews highlighted that there were sometimes challenges in accessing palliative care experience in community placements. The interviews were conducted during the Covid-19 pandemic and this had resulted in trainees having opportunities to gain additional experience in advance care planning. Conclusions: The study acknowledged that learning does not stop at CCT however the trainees generally felt that during training they received good preparation for independent practice in palliative care. The study supported the importance of good palliative care teaching and experience during training for managing both palliative care patients and providing transferrable holistic skills helpful in all aspects of clinical practice. Further work could be done to explore the variability of trainees' exposure to palliative care patients in the community and how trainers and practices could be supported in providing this experience.